2018
DOI: 10.1080/13607863.2018.1544212
|View full text |Cite
|
Sign up to set email alerts
|

The nature of decision-making in people living with dementia: a systematic review

Abstract: 1 Objective: The objectives of this systematic review were to: 1) understand how people 2 living with dementia are involved in making decisions; 2) explore the different 3 decisional styles and domains of decision-making that people living with dementia 4 experience and 3) identify what influences the level of decisional involvement of 5 people living with dementia.6 Methods: A systematic review of literature identified studies from Medline, PsycINFO, 7 HAPI and CINAHL databases. Search terms related to decisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 45 publications
0
22
0
1
Order By: Relevance
“…Agrawal et al [11] have demonstrated that spatial cognitive skills deteriorate with age, which leads to the impairment of the vestibular system. Moreover, the decisionmaking processes are also disturbed; thus, older people with cognitive impairment may be prone to selecting inappropriate strategies for maintaining balance [12]. it seems that the increased risk of falls in this population is a very complex problem.…”
Section: Introductionmentioning
confidence: 99%
“…Agrawal et al [11] have demonstrated that spatial cognitive skills deteriorate with age, which leads to the impairment of the vestibular system. Moreover, the decisionmaking processes are also disturbed; thus, older people with cognitive impairment may be prone to selecting inappropriate strategies for maintaining balance [12]. it seems that the increased risk of falls in this population is a very complex problem.…”
Section: Introductionmentioning
confidence: 99%
“…[for the person living with dementia] to have a friendly face for the first session". Similar to the systematic review findings, 16 several respondents spoke to the importance of including carers ("shared experiences make it easier and stop the feelings of isolation. Carers should also attend").…”
Section: Facilitators and Barriers To Engagementmentioning
confidence: 58%
“…Existing HOP literature was collated and summarized to formulate a theory of change based on the empirical evidence presented in randomized controlled trials (RCTs) and cross-sectional studies. A recent systematic review 16 was used to identify key features of decisionmaking processes for people living with dementia and understand how disclosure decision-making may take place in dementia.…”
Section: Phase One: Reviewing the Evidence Base And Theorymentioning
confidence: 99%
See 2 more Smart Citations